Decellularized scaffold-based poly(ethylene glycol) biomimetic vascular patches modified with polyelectrolyte multilayer of heparin and chitosan: preparation and vascular tissue engineering applications in a porcine model. Issue 7 (26th January 2022) - Gao, Huimin; Hu, Pengpeng; Sun, Gaoqi; Wang, Lei; Tian, Yu; Mo, Hong; Liu, Cheng; Zhang, Jun; Shen, Jian
Abstract : PEG/DCS surface was modified with heparin–chitosan PEM to construct a biomimetic vascular patch which could maintain long-term patency of the treated arteries in vivo . Abstract : Mechanical property mismatch between vascular patches and native blood vessels can result in post-operation failure; therefore, vascular patches that mimic the biomechanical properties of native blood vessels must be developed. In this study, we constructed a biomimetic vascular patch by coating a poly(ethylene glycol) (PEG) film onto a decellularized scaffold (DCS) and modifying its surface with a heparin–chitosan polyelectrolyte multilayer (PEM). The PEM-modified PEG/DCS vascular patches exhibited comparable mechanical characteristics with native blood vessels. They effectively resisted platelet adhesion, reduced the hemolysis rate, increased the clotting time in vitro, and favoured the adhesion and growth of endothelial progenitor cells. In addition, the modified patches maintained long-term patency (5 months) of the treated arteries in vivo . Because of the synergistic effect of heparin and chitosan in PEM, the vascular patches may be able to manage medical complications. Thus, the PEM-modified PEG/DCS vascular patches may have promising applications in the repair of damaged or diseased blood vessels.